2012
DOI: 10.1021/ac3021592
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Process of Lead Chromate in Paintings by Vincent van Gogh Studied by Means of Spectromicroscopic Methods. 4. Artificial Aging of Model Samples of Co-Precipitates of Lead Chromate and Lead Sulfate

Abstract: Previous investigations about the darkening of chrome yellow pigments revealed that this form of alteration is attributable to a reduction of the original Cr(VI) to Cr(III), and that the presence of sulfur-containing compounds, most often sulfates, plays a key role during this process. We recently demonstrated that different crystal forms of chrome yellow pigments (PbCrO(4) and PbCr(1-x)S(x)O(4)) are present in paintings by Vincent van Gogh. In the present work, we show how both the chemical composition and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
106
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(130 citation statements)
references
References 30 publications
18
106
1
5
Order By: Relevance
“…Several examples of the discoloration of synthetic yellow pigments from the turn of the twentieth century (e.g. zinc yellow (K 2 OÁ4ZnCrO 4 Á3H 2 O) [1], chrome yellow (PbCrO 4 ) [2][3][4][5][6], and cadmium yellow (CdS) [7,8]) have been recently reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples of the discoloration of synthetic yellow pigments from the turn of the twentieth century (e.g. zinc yellow (K 2 OÁ4ZnCrO 4 Á3H 2 O) [1], chrome yellow (PbCrO 4 ) [2][3][4][5][6], and cadmium yellow (CdS) [7,8]) have been recently reported.…”
Section: Introductionmentioning
confidence: 99%
“…They are known to be sensitive towards darkening when exposed to sunlight. [5] However, in a recent study, [6] it was found that the speed of the alteration process of the lead chromate based yellow paints is influenced both by their chemical composition (in terms of sulfate amount) and crystalline structure (monoclinic and/or orthorhombic): a profound darkening was observed only for those compounds containing a sulfur-rich solid solution of PbCr 1Àx S x O 4 (x ! 0.5) and those in which this compound is mainly present in the orthorhombic crystalline form.…”
mentioning
confidence: 99%
“…0.5) and those in which this compound is mainly present in the orthorhombic crystalline form. [6] Since different forms of the chrome yellow pigments were found to be present in several paintings by van Gogh, [3] this could provide a possible explanation why only some of the areas painted with this class of pigments appear darkened today. In recent years, a growing interest in the conservation of these paintings has arisen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfur-rich orthorhombic forms are more susceptible to browning. It has been postulated that PbCrO 4 and PbCr 1−x S x O 4 are more soluble when in the orthorhombic phase, and thus more chromate ions are available for redox reactions [25]. Table 2 shows the possible chrome yellow variants based on PbCr 1−x S x O 4 .…”
Section: Microfade Testingmentioning
confidence: 99%